Enterohemorrhagic Escherichia coli O157:H7 antigens produced in transgenic lettuce effective as an oral vaccine in mice - Su, Yun‑Lin (2023)
Enterohemorrhagic Escherichia coli (EHEC) O157:H7 is a food-borne pathogen where ruminant farm animals, mainly bovine, serve as reservoirs. Bovine vaccination has been used to prevent disease outbreaks, and the current method relies on vaccines subcutaneously injected three times per year. Since EHEC O157:H7 colonizes mucosal surfaces, an oral vaccine that produces an IgA response could be more convenient. Here, we report on oral vaccination against EHEC O157:H7 in mice orally gavaged with transgenic lettuce that produces EHEC O157:H7 antigens EspB and γ-intimin C280. Younger leaves accumulated a higher concentration of antigens; and in unexpanded leaves of 30-day-old T2 plants, EspB and γ-intimin C280 were up to 32 and 51 μg/g fresh weight, respectively. Mice orally gavaged with lettuce powders containing < 3 µg antigens for 6 days showed a mucosal immune response with reduced colonization of EHEC O157:H7. This suggests that the transgenic lettuce has potential to be used for bovine vaccination. To promote the biosafety of crop plants producing medically relevant proteins, recombination sites were built into our transgenic lines that would permit optional marker removal by Cre-lox recombination, as well as transgene deletion in pollen by CinH-RS2 recombination. The ability to upgrade the transgenic lettuce by stacking additional antigen genes or replacing older genes with newer versions would also be possible through the combined use of Bxb-att and Cre-lox recombination systems.